Survey report on awareness and participation behavior in disabled sports and disability understanding after Tokyo’s bid for the 2020 Olympics and Paralympics - Shiota, Kotomi (Journal of Physical Therapy Science, 2018)
[Purpose] This study analyzes awareness and participation behavior in disabled sports and disability understanding after Tokyo’s bid for the 2020 Olympics and Paralympics. [Subjects and Methods] The study conducted a cross survey on 220 registrants of an Internet research firm. It analyzed: the awareness of citizens and their behavioral changes, in the aftermath of the allocation of Olympic and Paralympic Games; subject attributes and education level; recognition of disabled sports; and the awareness and behavior of participants, with regard to disabled sports. The analysis was conducted using SPSS Ver. 21 (IBM). [Results] The subjects were not interested in watching (72.2%), participating (76.8%), or volunteering (71.8%) in disabled sports. In addition, 76.8% of the subjects exhibited no behavioral changes—such as by watching, participating, or volunteering in disabled sports—after the Olympics and Paralympics bid decision. [Conclusion] This study’s subjects had no confidence in their disability knowledge and no opportunities to interact with disabled persons. Furthermore, the bids for mega-events such as the Olympic and Paralympic Games did not lead to behavioral changes concerning disabled sports. Therefore, disability understanding should promote and deepen participation behavior in disabled sports.